Use of Helium/Oxygen Mixture in Noninvasive Ventilation During Urgent Tracheotomy for Upper Airway Compression: A Case Report. Issue 3 (1st February 2019) - Mathais, Quentin; Goutorbe, Philippe; Vatin, Loraine; Morvan, Jean Baptiste; Meaudre, Eric
Abstract : Ventilation or oxygenation can be difficult or even impossible in cases of upper airway obstruction. In this case report, we used a helium/oxygen mixture administered via noninvasive positive-pressure ventilation to perform an urgent tracheotomy under local anesthesia on a patient presenting upper airway compression. It improved his comfort and his stridor, facilitating supine positioning. This case describes another potential indication of the helium/oxygen mixture in noninvasive ventilation.